ADAPTASI PELAKSANAAN PERKULIAHAN MATA KULIAH PRAKTIK PEMBELAJARAN DALAM MASA PANDEMI COVID-19 - Setyo Eko Atmojo; Beny Dwi Lukitoaji (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2021)
This study aims to describe the process of teaching practical learning in SD and PKN SD courses. This research was conducted from September 2020 to January 2021 in the PGSD Study Program FKIP Universitas PGRI Yogyakarta. This research method is descriptive, data collection techniques through observation, questionnaires and documentation and descriptive data analysis. The results of the study show that the online lecture process as a form of adaptation to the Covid 19 pandemic is running well, which can be seen in the student response questionnaire where> 80% responded positively. The competency indicators for the subjects were achieved well, which was evident from the acquisition of an average grade of the subject indicators> 70 (Good).